Analisis Kompetensi Guru Bahasa Arab Tingkat Madrasah Aliyah di Kecamatan Cileunyi - Alamsyah, Tedi; Arifin, Muhammad; Romdoni, Moh Fahmi; F.A., Moch Hazmi (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2025)
Teachers are figures who carry the responsibility to realize the goals of national education, therefore teachers must have a comprehensive mastery of pedagogical, professional, personality, and social competencies, this study aims to determine the extent of the competence of Arabic language teachers at Madrasah Aliyah level in Cileunyi sub-district, this study uses a qualitative approach which is a research method that aims to explore and understand meaning, the primary data source of this research is Arabic language teachers of Madrasah Aliyah in Cileunyi, the results of research on professional competence with an average score of 89, pedagogic with an average score of 88, personality with an average score of 95 and social Arabic language teachers with an average score of 96, The acquisition of teacher competence scores from Madrasah Aliyah in Cileunyi is quite high, this shows that Arabic language teachers master the four competencies very well, this research can be a reference in future research studies.